(untitled) (Journal of Agricultural Engineering, 2017)
Biodegradable nanocomposite films are novel materials for food packaging because of their potential to extend the shelf life of food. In this research, the performance of cassava starch-zincnanocomposite film was evaluated for tomatoes packaging. The films were developed by casting the solutions of 24 g cassava starch, 0-2% (w/w) zinc nanoparticles and 55% (w/w) glycerol in plastic mould of 12 mm depth. The permeability of the films, due to water and oxygen, was investigated at 27°C and 65% relative humidity while the mechanical properties were determined by nanoindentation technique. The average thickness of the dried nanocomposite films was found to be 17±0.13 μm. The performances of films for tomatoes packaging was evaluated in comparison with low density polyethylene (LDPE; 10 μm) at the temperature and period ranges of 10-27°C and 0-9 days, respectively. The quality and microbial attributes of the packaged tomatoes, including ascorbic acid, β-carotene and total coliform were analysed at an interval of 3 days. The results revealed that the water vapour permeability increased while the oxygen permeability decreased with the nanoparticles (P<0.05). The hardness, creep, elastic and plastic works, which determined the plasticity index of the film, decreased generally with the nanoparticles. The films containing 1 and 2% of the nanoparticles suppressed the growth of microorganisms and retained the quality of tomatoes than the LDPE at 27°C and day-9 of packaging (P<0.05). The results implied that the film could effectively be used for tomatoes packaging due to their lower oxygen permeability, hardness, elastic and plastic works.